Azobenzene crystals swim on water surface triggered by light. Issue 38 (2nd June 2016) - Norikane, Y.; Tanaka, S.; Uchida, E.
Abstract : Crystals of 4-methoxyazobenzene move on water surface. The liquefied cis isomer acts as a fuel and light activates/deactivates the fuel. Abstract : Crystals of 4-methoxyazobenzene move on water surface and the motion is triggered by irradiation with ultraviolet light. The propulsion is produced by dissolution of the photo-generated cis isomer, which is produced by the photoinduced crystal–liquid phase transition. A photoresponsive boat was also prepared by a filter paper adsorbed with azobenzene.